Safety of a co-designed cognitive behavioural therapy intervention for people with type 1 diabetes and eating disorders (STEADY): a feasibility randomised controlled trialResearch in context - Marietta Stadler; Natalie Zaremba; Amy Harrison; Jennie Brown; Divina Pillay; Jacqueline Allan; Rachael Tan; Salma Ayis; Emmanouela Konstantara; Janet Treasure; David Hopkins; Khalida Ismail (The Lancet Regional Health. Europe)
Summary: Background: Safe management of people with Type 1 diabetes and EAting Disorders studY (STEADY) is a complex intervention for people with type 1 diabetes and mild-to-moderate disordered eating (T1DE) integrating cognitive behavioural therapy (CBT) with diabetes education. Aim was to test feasibility of STEADY in a randomised controlled trial. Methods: Feasibility parallel-group, randomised (blocks of four) controlled open-label trial (RCT) of STEADY against usual care (Control) at King's College London, UK. Participants were referred by clinicians or self-referred via social media advertisements. Forty adults with T1DE (Hba1c < 15%, body mass index 15–35 kg/m2, age ≥ 18 years) were randomised. STEADY was delivered in 12 sessions by a CBT-trained Diabetes Specialist Nurse through video-conferencing and mobile app. Main outcome at 6 months post-randomisation was feasibility. Baseline mental health data (Structured Clinical Interview for DSM-5, SCID-5RV), and secondary biomedical outcomes (HbA1c; glucose time in range; TIR) and person-reported outcome measures (PROM: Diabetes Eating Problems Survey-Revised, DEPS-R; Eating Disorder Examination Questionnaire Short, EDE-QS; Type 1 Diabetes Distress Scale, T1DDS; Generalised Anxiety Disorder Assessment, GAD-7; Patient Health Questionnaire, PHQ-9; Impact of Diabetes Profile, DIDP) were collected. Analyses were conducted as intention-to-treat. ClinicalTrials.gov NCT05140564. Findings: Of the 98 screened, 40 participants with T1DE were randomised (recruitment rate: 40.81%; 95% CI: 31.60%, 50.72%): 38 women, 1 man, 1 trans man (37 White, 1 White/Asian, 1 Black; 39 ± 11 years old, diabetes duration 22 ± 15 years, HbA1c 9.1 ± 2.6%). The drop-out rate was 3/20 = 15% (4.39%, 36.55%) in STEADY and 2/20 = 10% (1.57%, 31.32%) in Control. STEADY reported lower GAD-7 (5.75 ± 2.89 vs 10.18 ± 5.31, p = 0.0060) and higher DIDP (3.13 ± 0.63 vs 2.46 ± 0.87, p = 0.020) at follow-up compared with Control, indicating lower anxiety and higher diabetes-specific quality-of-life. Compared to baseline, STEADY improved in DEPS-R, EDE-QS, GAD-7, PHQ-9 and T1DDS. Interpretation: The STEADY-feasibility RCT demonstrated proof-of-concept for feasibility and mental health improvements in T1DE without deteriorating glycaemic control. A full scale RCT of STEADY will test effectiveness and implementation. Funding: National Institute for Health Research (CS-2017-17-023).